Direct Imaging of Cerebral Thromboemboli Using Computed Tomography and Fibrin-targeted Gold Nanoparticles - Kim, Jeong-Yeon; Ryu, Ju Hee; Schellingerhout, Dawid; Sun, In-Cheol; Lee, Su-Kyoung; Jeon, Sangmin; Kim, Jiwon; Kwon, Ick Chan; Nahrendorf, Matthias; Ahn, Cheol-Hee; Kim, Kwangmeyung; Kim, Dong-Eog (IVYSPRING INT PUBL, 2015)
Computed tomography (CT) is the current standard for time-critical decision-making in stroke patients, informing decisions on thrombolytic therapy with tissue plasminogen activator (tPA), which has a narrow therapeutic index. We aimed to develop a CT-based method to directly visualize cerebrovascular thrombi and guide thrombolytic therapy. Glycol-chitosan-coated gold nanoparticles (GC-AuNPs) were synthesized and conjugated to fibrin-targeting peptides, forming fib-GC-AuNP. This targeted imaging agent and non-targeted control agent were characterized in vitro and in vivo in C57BI/6 mice (n = 107) with FeCl3-induced carotid thrombosis and/or embolic ischemic stroke. Fibrin-binding capacity was superior with fib-GC-AuNPs compared to GC-AuNPs, with thrombi visualized as high density on microCT (mCT). mCT imaging using fib-GC-AuNP allowed the prompt detection and quantification of cerebral thrombi, and monitoring of tPA-mediated thrombolytic effect, which reflected histological stroke outcome. Furthermore, recurrent thrombosis could be diagnosed by mCT without further nanoparticle administration for up to 3 weeks. fib-GC-AuNP-based direct cerebral thrombus imaging greatly enhance the value and information obtainable by regular CT, has multiple uses in basic/translational vascular research, and will likely allow personalized thrombolytic therapy in clinic by a) optimizing tPA-dosing to match thrombus burden, b) enabling the rational triage of patients to more radical therapies such as endovascular clot-retrieval, and c) potentially serving as a theranostic platform for targeted delivery of concurrent thrombolysis.